Comorbidities and survival in patients with chronic hypersensitivity pneumonitis - Wälscher, Julia; Groß, Benjamin; Morisset, Julie; Johannson, Kerri A.; Vasakova, Martina; Bruhwyler, Jacques; Kreuter, Michael (Respiratory research, 2020)
Chronic Hypersensitivity Pneumonitis (cHP) is a fibrotic interstitial lung disease (ILD) resulting from repeated exposure to an offending antigen. Prognostication in cHP remains challenging, and the relationship between comorbidities and survival has yet to be characterized. The aim of this study was to describe the relationship between comorbid conditions and survival in patients with cHP.